Nursing problems of patients undergoing venous-venous ECMO therapy - Sabina Krupa; Hanna Krukowska-Sitek; Dorota Ozga (Kazimierz Wielki University, 2017)
ECMO (Extracorporeal Membrane Oxygenation) is an extracorporeal gas exchange method that, despite many, carries the risk of many complications. ECMO is a modern intensive care method which in many cases is the last resort for the patient. Care and supervision are provided by a multidisciplinary team of specialists: physicians, perfusionists, nurses. The aim of the article was to present ECMO nursing care and the principles of care and care during and after ECMO therapy